Methodology for Teaching Computer Science (Journal of Universal Science Research, 2024)
This paper discusses the various methodologies for teaching computer science, focusing on the most effective approaches and strategies to engage and educate students in this rapidly evolving field. Drawing on current research and best practices, the paper explores different teaching methods, curriculum design, and assessment techniques for enhancing student learning and skill development in computer science education.